Sex and fertility: wine as food and medicine in Hippocrates (5th- 4th centuries BCE) - Alexandre Aniceto, Bárbara (Romanitas - Revista de Estudos Grecolatinos, 2025)
This article explores bodily care in the Hippocratic Collection, especially the ones related to maintaining fertility among married people. Bodily care encompassed different dietary prescriptions so that food was part of a larger framework, in which both body procedures and diet were considered part of the Hippocratic treatment. Among the medical recommendations, one interests us particularly: wine’s internal uses as a remedy and food for the sick. From the intersection of the treatises On Ancient Medicine, Affections, Nature of Man and Sterility, alongside Aristophanes’ testimony, I analyze the Hippocratic dietary concept to grasp the connection between wine, sex, and fertility in Greek medicine of the classical period.